A SIMULATION MODEL FOR PLANNING A PUBLIC TRANSPORT USING ELECTRIC VEHICLES: A CASE OF PHETCHABUN RAJABHAT UNIVERSITY - Maneesaeng, Thanapat; Amdee, Noppadol; Phurahong, Nuttapon; Muangwai, Alongkorn (Life Sciences and Environment Journal, 2023)
The research's objective is to develop and study the behavior of public transport using electric vehicles from computer models under the conditions set by the university. The research process divides into two main parts: Part 1 is application. Metaheuristic Algorithms to find the appropriate sequence of travel routes, and part 2 is to develop and study the model. To assess the ability to assess service capability. The following indicators are observed, this includes the success of the service performance in conjunction with the waiting period, the amount of density in the queue, and the total length of time that the service recipient needs to be in the system. The model results show that the system can meet the needs of service users. However, considering the time lost on the trip, it was found that the average service time spent more than half an hour in a distance of fewer than five kilometers. The solution was to increase the frequency of service cycles. However, due to restrictions on the number of vehicles that are limited. Each round trip requires an average of 75.25 minutes. Therefore, to ensure that public transport can respond to customers effectively. The person in charge should increase the number of vehicles in line with the needs of the service users. However, the need for Phetchabun Rajabhat University to become a green university remains an important and challenging goal. This research demonstrates awareness of the university's environmental responsibilities and wants to stimulate activities to transform into a green university truly.